Evaluation of the Tran Medic Application Online in Outpatient Patient Registrtion at Royal Prima General Hospital Medan - Stephan, Weldy; Girsang, Ermi; Sihotang, Widya Yanti (The Islamic Education and Multiculturalism Foundation, 2025)
Data management and registration services are important components in supporting hospital information systems. Trans Medic application-based online registration is a web-based system that allows simultaneous use by multiple users. This study aims to evaluate the use of the Trans Medic online application in the outpatient registration process at Royal Prima Medan General Hospital. This research used a qualitative approach with a case study design. The informants in the study totaled ten people, consisting of one official staff, four registration officers, and five patients. Data were collected through in-depth interviews and analyzed using the stages of data reduction, data presentation, and conclusion drawing. The results showed that the obstacles faced in using the application were network disruptions and application errors that caused inability to access by patients and officers. Nevertheless, the human resources who manage the application are considered adequate and have the required knowledge and skills. This application provides significant benefits in the form of ease of registration for patients and work efficiency for officers. In addition, Standard Operating Procedures (SPO) related to the use of the application are available and running effectively.